Advanced Chemical Approaches for Environmental Sustainability: Innovations in Pollution Remediation and Green Chemistry - Sultani , Hussein Khudhair Hussein Abd; Farhan , Haider Aziz Karim; yousif , Mustafa Amer Hassan; Kashash , Mohammed Fawzi Kamel (American Journal of Biomedicine and Pharmacy, 2025)
The tremendous advances in chemical approaches to pollution remediation, bioremediation and genetic engineering, while exhibiting remarkable scientific innovations, have been and will continue to be revolutionary in chemical treatment methods for a more sustainable environment. The principles of green chemistry have provided a strong foundation for inventive chemical engineering to solve up-to-date industrial challenges associated with environmental sustainability. Easy-to-implement, on-demand, and sustainable chemical approaches to lower the pollution risk are practically important to achieve the goal of green and sustainable chemical industry. Pollutants exhibit a great variety of compositions, phases, and concentrations, which have required novel chemical approaches with specific ingenuity for their effective remediation. Over the years, great efforts have been dedicated to conduct basic studies to better understand the characteristics of the new instantaneous air pollution sources. It has become a common belief that volatile organic compounds (VOCs), which severely deteriorate air quality, are mainly released to the atmosphere from the fast-developing chemical industrial parks. The natural gas processing plants, oil and alkene field basins with over-800-kilometer-distance from populated cities bear a constant risk of releasing overwhelming quantities of aliphatic, aromatic, olefin, and alkyne hydrocarbon pollutants in accidents. Despite their serious hazards to air quality, health and environment, few advances have been made in conducting air pollution treatment studies that are only practical in the atmospheric background. It is of necessity to develop portable and catalytic converters with low processing temperature, long-term desorption active sites, and low-cost catalysts. Reactive chemical station could be designed with wires carrying customizable oxidation products from pre-customized upstream units, which divert formal changeover points into gradual peaks. Tracked points would disperse flow smoothly before being directed to matched oxidation units but amount more to nitro-products. Robust stoichiometric design could efficiently avert wide-formulated thermal runaway in reactor structures before long-distance transport to selective combustive reactors. Green bioremediation process is a sustainable biotechnology that uses microbes to eliminate waste pollution from contaminated environments. It draws from biological principles and design strategies that have evolved over the hundreds of millions of years of evolution on earth. In biological products biosorption/sequestration, contaminants are passively sorbed to cellular surfaces and then chemically modified through enzymatic reactions in biotransformation and bioaccumulation processes. The biological mechanism of the existing bioremediation methods and innovative and translational research into bioremediation by metabolic engineering and genetic engineering are discussed.